Serial point‐prevalence surveys to estimate antibiotic use in a small animal veterinary teaching hospital, November 2018 to October 2019. (13th November 2021) - Hsieh, Emmelyn S.; Bollig, Emma R.; Beaudoin, Amanda L.; Morrow, Anna; Granick, Jennifer L.
Abstract: Background: There is no standardized methodology to measure antibiotic drug use (AU) in small animal veterinary hospitals. Objectives: To estimate AU prevalence in a small animal veterinary teaching hospital and characterize usage by indication and evidence of infection. To establish an AU measurement methodology for veterinary settings. Animals: Electronic medical records of cats and dogs seen by primary care, urgent care, emergency and critical care, internal medicine, and surgery services during November 2018 to October 2019. Methods: On 1 day each month, data (signalment, visit reason, diagnostics, and antibiotic details, including indication) were collected for all animals seen on study services. Results: Of 168 inpatient dogs and 452 outpatient dogs, 98 (58.3%) and 107 (23.7%, ) were receiving at least 1 antibiotic on the day of data collection, respectively. For cats 15/49 (30.6%) inpatients and 29/187 (15.5%) outpatients were receiving at least 1 antibiotic. Common drug classes prescribed for dogs were potentiated penicillins (28.7%), first‐generation cephalosporins (22.1%), and nitroimidazoles (14.7%), and for cats, common drug classes administered were potentiated penicillins (26.9%), fluoroquinolones (13.5%), and penicillins (11.5%). Common indications for antibiotics included skin, respiratory, gastrointestinal, perioperative, aural, and urinary conditions. Conclusions and Clinical Importance: Serial point‐prevalence surveys (PPS) can estimate AU in a large specialty hospital setting and identify targets for antimicrobial stewardship. The methodology developed during this study can be adapted for use in private practice, including large animal practice. Mirroring methods used in human healthcare, the data collection tool can also be used to describe AU nationally through completion of national PPS.